The Effects of Product Quality and Interpersonal Communication on Customer Loyalty - Muhammad Tafsir; Roziana Shaari; Hasyim Muchtar; F Firmansya (International Journal on Advanced Science, Education, and Religion, 2018)
The rapid development of the business world today makes more and more companies are innovating the products sold, services provided and provide appropriate information to their customers to create a loyal consumer of the company. The purpose of this research is to analyze the effect of product quality, and interpersonal communication to consumer loyalty. The research method used is Simple Random Sampling with multiple linear regression analysis techniques. To ensure the accuracy of information, the number of population as much as 524 people are then drawn the number of samples as many as 100 people. The results showed that based on a simultaneous test (F test), product quality and interpersonal communication had the positive and significant effect to consumer loyalty but based on a partial test (t-test) there are different results where only interpersonal communication does not affect consumer loyalty. Interpersonal communication is not very influential on consumer loyalty and most importantly for consumers is the fulfillment of banking needs can be met without the presence of perceived difficulty.